Stroke care trends during COVID-19 pandemic in Zanjan Province, Iran from the CASCADE initiative: statistical analysis plan and preliminary results - Ghoreishi, Abdoreza; Arsang-Jang, Shahram; Sabaa-Ayoun, Ziad; Yassi, Nawaf; Sylaja, P. N.; Akbari, Yama; Divani, Afshin A.; Biller, Jose; Phan, Thanh; Steinwender, Sandy; Silver, Brian; Zand, Ramin; et al. (Elsevier, 2020)
Background The emergence of the COVID-19 pandemic has significantly impacted global healthcare systems and this may affect stroke care and outcomes. This study examines the changes in stroke epidemiology and care during the COVID-19 pandemic in Zanjan Province, Iran.